FUZZY NEUTROSOPHIC ROUGH SETS - Sweety, C. Antony Crispin (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper, we introduce Fuzzy Neutrosophic rough set and study some basic operations. Further we develop a systematic study on Fuzzy Neutrosophic rough set and obtain various properties induced by them. Some equivalent characterization and inter-relations among them are discussed. Keywords: Rough set, Neutrosophic set, Fuzzy Neutrosophic sets, Fuzzy Neutrosophic rough sets